Estimation of the Near Unit Root Model of Real Exchange Rates - McDermott, C. (Washington, D.C. : International Monetary Fund, 1996)
The time-series properties of real exchange rates, on a number of definitions, for 22 industrial countries during 1979-95 were used to re-examine whether PPP holds. It is shown that if real exchange rates reverted to a constant mean slowly, say by five percent a month, then at standard levels of significance we should expect 11 of the 22 series examined to yield evidence of mean reversion and to reject that hypothesis of a unit root. Using models that imply a constant unconditional mean or trend-stationary productivity changes, we find that only one of the 22 real exchange rates shows evidence against unit roots. This low rate of rejection of unit roots in real exchange rates can be construed as evidence against PPP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet